Pengaruh Brand Image dan Kualitas Produk terhadap Minat Beli Konsumen pada Agrowisata Usadha Puri Damai di Singakerta Ubud Gianyar Bali - putri, Dewa Ayu Karisma; Ayu Wimba, I Gusti; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the influence of brand image and product quality, on consumer buying interest in Usadha Puri Damai Agrotourism in Singakerta Ubud. The location of this study was conducted at Usadha Puri Damai Agrotourism in Singakerta Ubud with the number of samples in this study as many as 115 consumers who came to Usadha Puri Damai Agrotourism in Singakerta Ubud. The sampling method used in this study is the method using the accidental sampling method. Data collection methods are carried out through observation, interviews, documentation studies and questionnaires. The data analysis techniques used are multiple linear regression analysis, determination coefficient analysis, t significant test and F significant test. The result of this study is that brand image has a positive and significant effect on consumer buying interest in Usadha Puri Damai Agrotourism in Singakerta Ubud. Product quality has a positive and significant effect on consumer buying interest in Usadha Puri Damai Agrotourism in Singakerta Ubud. Brand image and product quality simultaneously have a positive and significant effect on consumer buying interest at Usadha Puri Damai Agrotourism in Singakerta Ubud. Advice that can be given is to promote more products sold and offered to consumers, such as through social media Instagram, Facebook